Effects of organic loading rate and hydraulic retention time on bioaugmentation performance to tackle ammonia inhibition in anaerobic digestion. (August 2021) - Christou, M.L.; Vasileiadis, S.; Karpouzas, D.G.; Angelidaki, I.; Kotsopoulos, T.A.
Graphical abstract: Highlights: Bioaugmentation performance is associated with increased OLR. Shortening of HRT did not appear to have a major effect on reactors performance. Methanosarcina prevailing in the inoculum was the success key of bioaugmentation. Correlation tests identified bacteria that interact with methanogens. Abstract: Three continuously stirred-tank reactors fed with manure operating under high ammonia levels (5.0 g NH3 -N L −1 ) and with increased organic loading rate (OLR), (2.09 R1, 3.02 R2 and 4.0 R3 g VS L −1 d −1 ), achieved through glucose amendment in R2 and R3, were inoculated with an ammonia-acclimatized microbial culture. Successful bioaugmentation was endured only in R2 and R3, both reactors characterized by high OLR, resulting in 19.6 and 24.5% increase in methane production, respectively. The high OLRs in these reactors favored the co-occurrence of the hydrogenotrophic ( Methanobacteriaceae ), methylotrophic ( Methanomethylophilaceae ) and aceticlastic methanogenic pathways. The latter was supported by the successful establishment of ammonium-tolerant Methanosarcina, prevailing in the inoculum. Oppositely in R1, the low OLR prevented the establishment of Methanosarcina, leading to an exclusive hydrogenotrophic methanogenesis and reduced methane production. HRT shortening resulted in limited effect on biomethane performance, indicating a well establishment of the introduced bioaugmentation culture in the reactors.